Analisis Efektivitas Penggunaan Facebook Adsense dan Search Engine Optimization (SEO) Sebagai Media Digital Marketing Dalam Meningkatkan Traffic Kunjungan Platform Startup Ajarinaja.com - Muhammad Amirul Asraf (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted to determine the effectiveness of digital marketing with the implementation of Facebook Ads and the implementation of Search Engine Optimization (SEO). The purpose of this study is to determine the implementation of digital marketing strategies including paid marketing (Facebook Ads) whose success is measured by Facebook Ads Manager and organic marketing (Search Engine Optimization) whose success is measured by Google Analytics, to increase traffic to the startup platform Ajarinaja.com. from the perspective of the Ajarinaja.com Startup Platform manager. As well as knowing the results of the comparison of the effectiveness of digital marketing using Key Performance Indicators (KPI) digital marketing between paid marketing using Facebook Ads and organic marketing using the implementation of Search Engine Optimization (SEO) in increasing traffic to visit the Ajarinaja.com startup platform. This type of research is descriptive research with a qualitative approach and interviews with the Startup Ajarinaja.com team, namely digital marketing, SEO article writers and graphic design. The informant determination technique used is purposive sampling technique. The focus of research in this research includes 1) Implementation of digital marketing strategies which include paid marketing (Facebook Ads) and organic marketing (Search Engine Optimization); 2) Comparison of the effectiveness of digital marketing strategies between Facebook Ads as paid marketing and Search Engine Optimization (SEO) as organic marketing on the Ajarinaja.com Startup Platform.The results of this study show that the implementation of digital marketing in paid marketing using Facebook Ads for the Ajarinaja.com Startup Platform is more effective, compared to using Search Engine Optimization (SEO). Although Search Engine Optimization will provide impact visitors to the Ajarinaja.com Startup Platform in the future, but with the condition of the Ajarinaja.com Startup Platform which is still a new Startup Platform at this time, of course, the SEO strategy used still does not have a big impact when compared to the “paid marketing method'.